Socio-economic Status of Gandharva Community Living in Batulechaur, Pokhara - Dhungana, Ananta Raj (Journal of Development and Social Engineering, 2017)
This study aims to explore the socio-economic status of Gandharva community. For this purpose, the household heads of all the fifty households of Gandharva community of Batulechaur in Pokhara were interviewed by using structured questionnaire. Descriptive statistics was used for analyzing the information gathered from the respondents. The study focused on socio-economic status and occupational shift of Gandharva community. The study found that the Gandharva community is socially marginalized and relatively poor in comparison to other communities. Their living status is not good. They have low education and low income profession as reason. For this reason most of them have shifted their occupations from singing and dancing to others like service sector, unskilled job, foreign employment in golf countries and some small business like running shops, vegetable selling, etc.